Summer Grazing of Steers in Western Kansas - Dumler, Troy J.; Jones, Rodney (My University, 2004)
This publication is a guide to budget estimate costs and returns for a season-long and an early-intensive grazing system in Western, KS.
MF1007_2004-10
Keywords: MF1007; Economics; Livestock; MF